2013
DOI: 10.1128/aac.00958-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Fluoroquinolone and Azole Use on QT Prolongation in Hematology Patients

Abstract: bQTc prolongation is a risk factor for development of torsades de pointes (TdP). Combination therapy with fluoroquinolones and azoles is used in patients with hematologic malignancies for prophylaxis and treatment of infection. Both drug classes are implicated as risk factors for QTc prolongation. The cumulative effect on and incidence of QTc prolongation for this combination have not been previously described. A retrospective chart review was performed with hospitalized inpatients from 1 September 2008 to 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
0
39
0
1
Order By: Relevance
“…Zeuli et al . recommended that these haematology patients are monitored extensively . In line with this study, ciprofloxacin has recently been added to the list of QTc‐prolonging drugs with a known risk of TdP according to the CredibleMeds® QT drug list by the AZCERT .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Zeuli et al . recommended that these haematology patients are monitored extensively . In line with this study, ciprofloxacin has recently been added to the list of QTc‐prolonging drugs with a known risk of TdP according to the CredibleMeds® QT drug list by the AZCERT .…”
Section: Introductionmentioning
confidence: 75%
“…Zeuli et al . studied the effect of fluoroquinolone and azole therapy on QTc prolongation in 94 haematology patients. In this retrospective study, 21 (22%) patients had clinically significant changes from baseline in the QTc interval, and several associated risk factors were found, such as hypokalaemia ( P = 0.03) and a left ventricular ejection fraction of <55% ( P = 0.02).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it can result in modification of the cardiac clinical symptoms related to one or both of them. Both, epidemiological studies and adverse reaction reporting systems data confirm that DDIs are one of the common additional risk factors for reported QT prolongation or TdP (Boyce, Baisley, & Warrington, ; Heist & Ruskin, ; Katoh et al, ; van der Sijs et al, ; Zeuli, Wilson, & Estes, ). An example of the drug‐triggered QT prolongation resulting from the interaction between drugs is combination of terfenadine and ketoconazole (KETO).…”
Section: Introductionmentioning
confidence: 92%
“…[64][65][66] These incidents were confirmed in larger cohort studies. [67][68][69] An experimental study suggested substantial inhibition of hERG potassium channels by fluconazole, which might induce acquired LQTS and thereby explain the potential proarrhythmic effect. 70 However, this study was conducted in human isolated kidney cells and not myocardial tissue.…”
Section: Antimicrobial Drugsmentioning
confidence: 99%